Single immersion in cold water below 4 °C: A health hazard in young healthy men? - Aneta Teległów; Iwona Cicha (PLoS ONE)
The circulatory system plays a significant role in the adaptation of the human body to varying environmental conditions and stress factors, such as cold water immersion. The aim of the study was to determine whether a single immersion in cold water below 4 °C, at air temperature of -15 °C constitutes a health risk in young healthy men. For this purpose, the following parameters were determined in the blood samples collected in 13 young males before and after cold water immersion: electrolytes, renal profile, liver profile, lipid profile, glucose, testosterone, thyroid-stimulating hormone, cortisol. After the immersion, a statistically significant decrease was found for Cl- (p ≤ 0.027), mean values of renal profile indicators: urea (p = 0.0019), creatinine (p = 0.0007), and uric acid (p = 0.0293), as well as testosterone (p = 0.000037). In turn, higher values of estimated glomerular filtration rate (p = 0.0425), total bilirubin (p = 0.0033), aspartate transaminase (p = 0.0023), alanine transaminase (p = 0.0053), lactate dehydrogenase (p = 0.0336), creatine kinase (p = 0.0117), CK-MB isoenzyme of creatine kinase (p = 0.0028), and high-density lipoprotein (p = 0.0270) were measured after cold water immersion. No significant changes in other biochemical parameters were observed. Single cold water immersion thus resulted in significant changes of blood parameters within non-pathological limits.